Review of Dalhousiella McIntosh, 1901 (Annelida: Hesionidae) - Salazar-Vallejo, Sergio I.; Rizzo, Alexandra (Cahiers de Biologie Marine, 2020)
Among hesionid annelid genera, Dalhousiella McIntosh, 1901 is a poorly known abyssal group. For example, the delineation of species belonging to it has not been settled, and the affinities to other hesionin genera deserve clarification. Further, type material for the type species, D. carpenteri McIntosh, 1901 is lost, and the only syntype available of the second species, D. hesionoides (Augener, 1906) is partially dried-out. In order to clarify the generic delineation, non-type specimens of both species were studied. This allowed us to understand the development of nuchal organs, redelineate the morphological pattern for the genus group name, and characterize the morphology of the two known species. The lack of topotype specimens made us postpone the proposal of a neotype for the type species. A key for identifying Dalhousiella species might help assess their presence in other oceanic basins.
World Polychaeta Database (WPolyDb). There is no ZooBank registration. The journal is online only. The article contains no nomenclatural acts